Peran Konjungsi Dalam Kalimat Majemuk Bahasa Indonesia - Gede Adistana Wira Saputra; Vitalia Hanako Murni Simanjuntak; Runi Fazalani; I Made Darma Sucipta (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
This study aims to analyse the role of conjunctions in Indonesian compound sentences based on their types and syntactic functions. The data source for this research was obtained from various linguistic references, particularly Tata Bahasa Baku Bahasa Indonesia (The Standard Grammar of Indonesian) Fourth Edition (2017), as well as other supporting literature discussing conjunctions in the Indonesian language. Data collection was conducted through a literature review using observation and note-taking techniques, where all identified conjunctions were classified based on their types and functions in clause relationships. The collected data were then analyzed using a descriptive-synchronic method with a syntactic classification approach to determine the usage patterns of conjunctions in compound sentences. The results of the study indicate that Indonesian has 110 conjunctions, which can be categorized into four main types: (1) coordinating conjunctions, which connect equivalent elements within a sentence; (2) correlative conjunctions, which link two elements with the same syntactic structure; (3) subordinating conjunctions, which connect a main clause with a subordinate clause in a hierarchical relationship; and (4) inter-sentential conjunctions, which logically connect two sentences within a discourse. Further analysis reveals that the appropriate use of conjunctions significantly influences the clarity of meaning and logical structure in compound sentences.